Resveratrol supplementation during in vitro maturation improves embryo development of prepubertal goat oocytes selected by brilliant cresyl blue staining - Anna-Rita PIRAS; Irene MENÉNDEZ-BLANCO; Sandra SOTO-HERAS; Maria-Gracia CATALÁ; Dolors IZQUIERDO; Luisa BOGLIOLO; Maria-Teresa PARAMIO (The Society for Reproduction and Development, 2018)
This study aimed to investigate the effect of resveratrol supplementation in maturation medium on the developmental ability and bioenergetic\oxidative status of prepubertal goat oocytes selected by brilliant cresyl blue (BCB). Oocytes collected from slaughterhouse-derived ovaries were selected by 13 µM BCB staining and classified as grown BCB+ and growing BCB- oocytes. All oocytes were matured in vitro in our conventional maturation medium and supplemented with 1 µM (BCB+R and BCB-R) and without (Control groups: BCB+C and BCB-C) resveratrol. After 24 h, IVM-oocytes were fertilized with fresh semen and presumptive zygotes were in vitro cultured for 8 days. Oocytes were assessed for blastocyst development and quality, mitochondrial activity and distribution, and levels of GSH, ROS, and ATP. BCB+R (28.3%) oocytes matured with resveratrol presented significantly higher blastocyst development than BCB+C (13.0%) and BCB- groups (BCB-R: 8.3% and BCB-C: 4.7%). Resveratrol improved blastocyst development of BCB-R oocytes at the same rate as BCB+C oocytes. No differences were observed in blastocyst quality among groups. GSH levels were significantly higher in resveratrol groups (BCB+R: 36554.6; BCB-R: 34946.7 pixels/oocyte) than in control groups (BCB+C: 27624.0; BCB-C: 27655.4 pixels/oocyte). No differences were found in mitochondrial activity, ROS level, and ATP content among the groups. Resveratrol-treated oocytes had a higher proportion of clustered active mitochondria in both BCB groups (BCB+R: 73.07%; BCB-R: 79.16%) than control groups (BCB+C: 19.35%; BCB-C: 40%). In conclusion, resveratrol increased blastocyst production from oocytes of prepubertal goats, particularly in better quality oocytes (BCB+).